USO DA TEORIA DO FUNCIONAL DE DENSIDADE NA ANÁLISE DE SPIN CROSSOVER EM AULAS DE QUÍMICA INORGÂNICA - Pougy,Karina de Carvalho (2020)
Spin crossover is a property found in some coordination compounds formed by the first series of transition metals with d4-d7 configuration. These complexes, when stimulated by an external factor (temperature, light, etc.), can be converted from their low spin states to high spin states, or vice versa. However, this issue is not addressed in the Inorganic Chemistry literature used in undergraduate courses. In this work, the Density Functional Theory is used to predict which complexes may present the Spin Cross Over property. In addition to establish a methodology to predict in which situations this process will occur, this computational tool can also be used in undergraduate or postgraduate classes to explore this property in the study of coordination compounds.